Effects of trypanosomiasis on growth and mortality of young East African Zebu cattle exposed to drug-resistant trypanosomes - Rowlands, G.J.; Mulatu, W.; Authié, Edith; D'Ieteren, G.D.M.; Leak, S.G.A.; Nagda, S.M. (Elsevier, 1994)
Approximately 390 East African Zebu calves from birth to 3 years of age and their dams were monitored monthly from 1986 to 1992 in nine village herds in an area of high trypanosomiasis risk in southwest Ethiopia where there was resistance to all available trypanocidal drugs. Cattle were individually treated with diminazene aceturate when they were detected to be parasitaemic and their packed red cell volume decreased below 26 percent, or when they showed clinical signs of trypanosomiasis. The average monthly trypanosome prevalence among cattle between 6 and 36 months of age was 18 percent. Within this environment, animals achieved averaged body weights of 79+14 (SD) kg, 134+21 kg and 183+22 kg at 12, 24 and 356 months of age respectively. Annual mortalities ranged from 8 to 24 percent, from 6 to 15 percent and from 4 to 16 percent in the age ranges 0-12, 13-14 and 25-36 months respectively. Calves parasitaemic in any one month in 1988, when early rains failed, had a higher average mortality in that month (3.1 percent) than those that were aparasitaemic (1.4 percent). Liveweight gains of calves born to the dams detected as parasitaemic on more than half the occasions during the first 6 months postpartum were 14 percent lower than those of calves from dams not detected as parasitaemic over this period. An effect of parasitaemia in the calf on weight gain to 12 months could not be demonstrated, but animals detected as parasitaemic on more than six of the 12 monthly samples between 13 and 24 or 245 and 36 months of age had growth rates on average 22 percent lower than those of animals not detected as parasitaemic. All these effects of trypanosomiasis on productivity, however, were temporary and animals later compensated for periods of poor growth. Regualr trypanocidal chemotherapy in a situation of high levels of drug resistance may have helped to maintain the health and productivity of these young cattle.